Laryngeal mucosa of head and neck cancer patients shows increased DNA damage as detected by single cell microgel electrophoresis - Schmezer, Peter; Bartsch, Helmut (Toxicology, 2000)
Major risk factors for cancer of the oral cavity, pharynx and larynx are smoking and excess alcohol consumption. Since long-term survival rates of head and neck cancer patients have not substantially been improved, new preventive strategies including the use of cancer chemopreventive agents have to be developed. With the aim of developing biomarkers which can verify the efficacy of chemopreventive interventions, a standardised alkaline microgel electrophoresis (MGE) assay was applied as a sensitive and rapid tool to detect DNA damage on a single cell level. Macroscopically normal laryngeal mucosa biopsies obtained by surgery from head and neck cancer patients (n=29) and from hospital controls (n=22) were analysed by MGE in a pilot study. As compared to controls, cells from head and neck cancer patients showed a significantly elevated DNA damage without any further genotoxic treatment (P<0.01). We conclude that this increased background DNA damage in laryngeal epithelia could result from genetic alterations caused by smoking and alcohol leading, in accord with the field cancerisation hypothesis, to a gradual decrease of genomic stability and malignancy. MGE should now be explored as a rapid screening method in larger clinical studies: (i) to identify high-risk subjects carrying cells with decreased genomic stability and (ii) to verify the efficacy of chemopreventive regimens to prevent or slow down the development of head and neck cancer in high-risk persons.
Gesehen am 02.02.2021